Perspectives and Development of Electrical Systems in More Electric Aircraft - Ahmet Yigit Arabul; Emre Kurt; Fatma Keskin Arabul; İbrahim Senol; Martin Schrötter; Róbert Bréda; Dávid Megyesi (International Journal of Aerospace Engineering)
On-board electrical systems are the key components of each modern aircraft. They enable its safer, more comfortable, and environmentally friendlier operation. The strict regulations to reduce pollution and noise are produced by aircraft eventuated in projects like Clean Sky or ICAO Global Coalition for Sustainable Aviation. One solution to environmentally friendlier operation is the full electric propulsion of the aircraft, which enables the reduction of both noise and pollution. Such a concept requires a total change of all on-board power systems and enables the profound change in aircraft design. This paper presents the evolution of aircraft power systems into the so-called more electric aircraft (MEA) and discusses the state-of-the-art electrical systems. Furthermore, the concept of all-electric aircraft (AEA) is presented here.